EPISTEMOLOGI AHLI WARIS PENGGANTI DALAM KOMPILASI HUKUM ISLAM - Hajar M. (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2014)
Kompilasi Hukum Islam (KHI) regarded as ijma of Indonesian ‘ulama fiqh schools were formulated through the study of the books of fiqh, interviews with scholars, jurisprudence and comparative study in Muslim-majority countries. Substantially, KHI includes legal reform, among others, the heir replacement in Article 185. The existence of substitute heirs still polemical, both in terms of the origin and validity. Heir rreplacement in KHI formulated through the jurisprudence derived from customary law derived from the Civil Code Napoleon in France. Substitute heirs grown in resolving inheritance cases, both at the level of the heirs, the level of customary deliberation and the judiciary. Results of this study showed that the presence of substitute heirs is a culture that is not based on faith, contrary to the principle of fairness, the principle ijbari, not in line with elements of inheritance and also contrary to the principle of the primacy and hijab. Heir replacement in KHI needs to be revisited.